Peran Pendidikan Karakter dalam Meningkatkan Prestasi Akademik Siswa pada MIN 19 Bireuen - Amar Halim (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This study aims to determine the implementation of character education, the efforts of teachers to implement character education to improve student learning outcomes, and the supporting and inhibiting factors for the implementation of character education in MIN 19 Bireuen students. The study uses a qualitative approach with a phenomenological design. Data collection techniques used were observation, interviews, and documentation. The subjects of this research were the principal, teachers, and students of MIN 19 Bireuen. The results showed that character education was implemented through the integration of character values into the curriculum, learning activities, and school culture. Teachers strive to implement character education by providing exemplary role models, creating a conducive learning environment, and involving students in character-building activities. Supporting factors include commitment from the school leadership, teacher professionalism, and parental involvement. While the inhibiting factors are the limited time allocation for character education, the lack of teaching resources, and the diverse student backgrounds. This research is expected to contribute to developing character education in schools and improving student learning outcomes.